Source parameters estimation of the 1980 Bajhang Earthquake, far western Nepal - Khanal, K. N. (Journal of Nepal Geological Society, 1997)
The Bajhang earthquake of 1980 is one of the moderate magnitude earthquakes in the Himalaya that has been investigated by many researchers. The methods used by them for determining source parameters vary from the use of the first motion data to the waveform modeling. The ambiguity in focal mechanisms determined by different processes has been resolved by comparing the synthetic seismograms generated using wavenumber integration technique with those observed at the Global Digital Seismograph Networks (GDSN).The earthquake source parameters determined are found to be as follows: Dip=26°, Strike=290°, Rake=90°, Depth of focus=20±5 km and source time function=7 (2, 3, 2) seconds.